CULTURE OF RECEIVING POLITICAL INFORMATION IN THE INFORMATION SOCIETY (American Journal of Pedagogical and Educational Research, 2023)
This article analyzes the role of information culture, highlighting the role of education, mass media and communications, and the Internet in ensuring personal political security.